2019
DOI: 10.1093/ofid/ofz330
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of the M184V/I Mutation on the Efficacy of Abacavir/Lamivudine/Dolutegravir Therapy in HIV Treatment-Experienced Patients

Abstract: Background The impact of the M184V/I mutation on the virological failure (VF) rate in HIV-positive patients with suppressed viremia switching to an abacavir/lamivudine/dolutegravir regimen has been poorly evaluated. Methods Observational study from five European HIV cohorts among treatment-experienced adults with ≤50 copies/mL of HIV-1 RNA who switched to abacavir/lamivudine/dolutegravir. Primary outcome was the time to first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 30 publications
5
27
1
Order By: Relevance
“…Our study highlights the virological efficacy of DTG+2NRTIs combination therapy with only 3.2% of patients who discontinued the regimen due to VF during the time of observation. This finding is in line with the virological efficacy of DTG based regimens reported in observational studies with a mixed population of patients harbouring or not resistance to NRTIs [15,16,19].…”
Section: Immune-virological Status and Years On Art No Significant Asupporting
confidence: 85%
See 3 more Smart Citations
“…Our study highlights the virological efficacy of DTG+2NRTIs combination therapy with only 3.2% of patients who discontinued the regimen due to VF during the time of observation. This finding is in line with the virological efficacy of DTG based regimens reported in observational studies with a mixed population of patients harbouring or not resistance to NRTIs [15,16,19].…”
Section: Immune-virological Status and Years On Art No Significant Asupporting
confidence: 85%
“…Second, the high discontinuation rate and the median time of observation of only 12 months did not allow to assess the long term impact of NRTIs mutations. Third, a very few VFs were observed despite our conservative definition of VF, although in line with the rate reported in previous works[15,16]. Finally, when considering the K65R mutation, a type 2 error cannot be excluded due to the low number of cases and consequently our findings should not be generalized to such patients.According to our findings, the risk of VF after switching to DTG+2NRTIs appears to be low.Previous NRTIs mutations seem to have no impact on the risk of VF in patients under virological control on ART regimens based on DTG+2NRTIs.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…16 Of note, the patients in this trial had only the M184V/I mutation, unlike the population in our study which often had multiple resistance-conferring mutations present. Olearo et al 17 retrospectively examined switching to a regimen containing ABC, 3TC, and DTG in treatment-experienced patients and found that the M184V mutation, present in 137 patients (8.4% of study population), was not associated with increased risk of virologic failure. Finally, Sahloff and colleagues retrospectively evaluated the use of boosted DRV plus TDF/FTC in 32 treatment-experienced patients with at least an M184V/I mutation.…”
Section: Discussionmentioning
confidence: 99%